Comparative pharmacokinetics and bioavailability of brimonidine following ocular and dermal administration of brimonidine tartrate ophthalmic solution and gel in patients with moderate‐to‐severe facial erythema associated with rosacea. (1st July 2014) - Benkali, K.; Leoni, M.; Rony, F.; Bouer, R.; Fernando, A.; Graeber, M.; Wagner, N.
Summary: Background: Persistent facial erythema is the most common primary pathological feature of rosacea, the only treatment for which is brimonidine tartrate (BT) gel. Objectives: To assess the relative bioavailability of topical BT gel in comparison with the ophthalmic BT solution. Methods: A pharmacokinetic study was conducted to compare intraindividual systemic exposures after dermal application of BT gel (0·07%, 0·18% and 0·5%) under maximal use conditions in patients with moderate‐to‐severe facial erythema associated with rosacea, and administration of BT ophthalmic solution 0·2%. Results: Patients who received BT ophthalmic solution 0·2% three times a day for 1 day had a mean C max of 54 ± 28 pg mL −1 and a mean 0–24‐h area under the curve (AUC0–24 h ) of 568 ± 277 pg h mL −1 . Topical application of BT gel for 29 days resulted in quantifiable systemic exposure in 22%, 48%, 71% and 79% of patients who received BT gel 0·07% twice daily, 0·18% once daily, 0·18% twice daily and 0·5% once daily, respectively. The mean C max values for the BT gels ranged between 13 and 25 pg mL −1, and mean AUC0–24 h values ranged between 42 and 290 pg h mL −1 . Systemic exposure increased with applied dose, with no drug accumulation for the duration of treatment. The systemic exposure observed with the highest dose of BT gel (0·5% once daily) was significantly lower than the systemic levels observed for the ophthalmic solution. 0·2% apply for all the concentrations. Conclusions: The systemic safety profile of BT gel may be considered better than that of the ophthalmic solution.